Bandwidth enhancement of Vivaldi antenna using triangular shaped slots - Wan Ahmad Khairuddin, Wan Nur Aqilah; Othman, Mohd Azlishah; Noor Azizi, Muhammad Syafiq; Yaakob, Mazri; Ramli, Mohamad Hafize (Universiti Teknologi Malaysia, 2016)
This paper discusses about a bandwidth enhancement of Vivaldi antenna loaded using triangular shaped. Firstly, a normal Vivaldi antenna using FR-4 substrate had been designed.Then, the triangular shaped slots had been added at the upper layer of the antenna.It shows the better improvement in return loss, gain, directivity and bandwidth operated at frequency of 10 GHz after the addition of the triangular shaped slot.The advantages of a Vivaldi antenna such as simplicity, wide bandwidth, and high gain at microwave.The return loss of this Vivladiantenna with triangular slot is – 18.495 dB at resonant frequency of 10 GHz while for Vivaldi antenna is – 17.818 dB at 10 GHz for measurement result.This proposed antenna had been designed and simulated using Computer Simulation Technology (CST) simulation software.